2015
DOI: 10.1517/14728222.2015.1057569
|View full text |Cite
|
Sign up to set email alerts
|

MiR-199a-5p and miR-375 affect colon cancer cell sensitivity to cetuximab by targeting PHLPP1

Abstract: This study proposes miR-199a-5p and miR-375 as contributors to CTX resistance in colon cancer and suggests a novel approach based on miRNAs as tools for the therapy of this tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…[29][30][31] Liu et al demonstrated miR-451a sensitized breast cancer to Tamoxifen and inhibited growth of breast cancer cells. In addition, Mussnich et al 32 illustrated miR-199a-5p and miR-375 reduced colon cancer sensitive to CTX. Our results showed the expression of miR-551a was up-regulated in the SKOV3 cells treated with DMC.…”
Section: Discussionmentioning
confidence: 98%
“…[29][30][31] Liu et al demonstrated miR-451a sensitized breast cancer to Tamoxifen and inhibited growth of breast cancer cells. In addition, Mussnich et al 32 illustrated miR-199a-5p and miR-375 reduced colon cancer sensitive to CTX. Our results showed the expression of miR-551a was up-regulated in the SKOV3 cells treated with DMC.…”
Section: Discussionmentioning
confidence: 98%
“…MicroRNA array showed that microRNA-195 chemosensitizes CC cells to the chemotherapeutic drug doxorubicin by targeting the first binding site of B-cell CLL/lymphoma 2-like protein 2 (bCL2L2) mRNA (29). Mussnich et al reported that miR-199a-5p and miR-375 affect CC cell sensitivity to cetuximab by targeting the PH domain and leucine rich repeat protein phosphatase 1 (PHLPP1) (30). MicroRNA-425-5p was also reported to reduce 5-FU resistance in colorectal cancer cells via the regulation of programmed cell death 10 (21).…”
Section: Mir-20b Reduces 5-fu Resistance In the Hct116-r Cellsmentioning
confidence: 99%
“…It is not clear how miR-22 mediates activation of PTEN only in muted but not wide-type p53 cells. Similarly, miR-199a-5p and miR-375 increase resistance to cetuximab in CRC partially due to their repression of a common target PHLPP1, a tumor suppressor that negatively regulates the AKT pathway (Mussnich et al, 2015). Studies have shown KRAS mutations are correlated with acquired resistance to anti-EGFR therapy in CRC (Misale et al, 2012).…”
Section: Apoptosismentioning
confidence: 99%